KUALITAS MINYAK BIJI KARET SEBAGAI MINYAK PANGAN ALTERNATIF PASCA PENGHILANGAN HCN - Karima, Rizka (Kementerian Perindustrian, 2015)
The rubber seeds (Hevea brasiliensis) can be used because rubber seed contains a high fat or oil contain so that it can be utilized as being edible oil. However, the problem is the presence of Hydrogen Cyanide (HCN) toxic compound in the rubber seeds which is so dangerous. Cyanide acid it can be reduces with soaking and boiling process. The purpose of this research were to known quality of rubber seeds. Rubber seeds oil was produced after HCN content was reduced. Mean yield of rubber seeds was 20,13%. Quality testing is done with a few key parameters on which oil fatty acid composition, acid number, peroxide number and iodine number. Total saturated fatty acid content was 14.1% and an unsaturated fatty acid was 85.9%, the mean value of the acid number was 4.19 mgKOH / g, peroxide value MeqO 11.17 / kg and iodine number of 140 g iodine / 100 g. These results indicate that good quality oil for edible oils when compared with the standard.Keywords : rubber seeds, rubber seeds oil, edible oil